Pemanfaatan Cangkang Telur dan Sekam Padi Sebagai Bioadsorben Metilen Biru pada Limbah Tekstil - Lestari, Naning Citra; Budiawan, Ilham; Fuadi, Ahmad Muhammad (Universitas Andalas, 2021)
The textile industry in Indonesia has increased since the 1980s. From the non-oil and gas sector, the textile industry is the government's largest source of income. In addition to its impressive growth, about 10-15% of the used textile dyestuff is wasted at the dyeing process can exceed the maximum Chemical Oxygen Demand level of 150 mg/L. Synthetic dyes contain carcinogenic ingredients that can harm the environment and aquatic biota. The alternative for handling the dye waste is the adsorption method using bio adsorbent from a mixture of chicken eggshells and rice husk ash. Both have the potential to be used as adsorbents because they have an active site, abundant amounts, and are economical. This study was to determine the effect of the process variables of the adsorbent mass ratio, contact time, and pH on the adsorption capacity of methylene blue using a mixture of eggshells and rice husk ash with the UV-Vis Spectrophotometer analysis method. The results showed that the optimal conditions for the adsorption of 20 ppm methylene blue were 0.2:0.8 gram of adsorbent ratio, 80 minutes, and pH of 3. The adsorption capacity obtained was 98.817%, reduced the methylene blue concentration to 0.237 ppm.Â